El Salvador : 2016 Article IV Consultation- Press Release; Staff Report; and Statement by the Executive Director for El Salvador. (IMF Staff Country Reports; Country Report ;, 2016)
This paper focuses on policies to raise growth; underpin fiscal sustainability while enhancing social safety nets; and strengthen financial sector stability, deepening, and inclusiveness. GDP growth has averaged 2 percent during 2000-14, well below the Central American regional average of 4 1\2 percent. While the underlying causes of the low growth are complex, a key channel through which they are expressed appears to be low investment. Given the need to increase growth, revenue-raising measures should be accompanied by cuts in distortionary taxation. Stress tests suggest that financial buffers are adequate to contain most risks. The financial deepening and advancing financial inclusion could have a meaningful impact on both growth and poverty.